STUDY OF OPTICAL PROPERTIES CHANGING BY THE TEMPERATURE INFLUENCE IN THE «POLYMER-HIGH-TEMPERATURE SUPERCONDUCTOR» SYSTEM - Kupchishin, A.I.; Muradov А.D.; Taipova, B.G.; Sarsembaev, G.B. (Recent Contributions to Physics, 2008)
The influence of low temperature on the optical properties of polyimide films and its polymeric composition (PC) with powder filler of high-temperature superconductor (HTS) YBa2Cu3O6+x (where x=0,7) and concentration: 0,05%;0,01%; 0,5% were investigated. The optical characteristics were studied in spectral range 190-1100 nm on spectrophotometer SF-2000. It was established, that the cooling by liquid nitrogen causes the reduction of light-transmission coefficient on 3-6%, but there is no any changing in optical dencities, and it may be because of the decreasing of free ions concentrations in the polyimide film structure. For PC with HTS filler 0,05%; 0,1% light-transmission coefficient after cooling remains unchangeable, but for concentration with 0,5% the increase light-transmission factor on 15% was found. These facts are evidence of processes with inverse re-structural changing’s.